Writing the Forest in Early Modern England : A Sylvan Pastoral Nation - Theis, Jeffrey S. (Medieval and Renaissance literary studies., 2009)
"An ecocritical study of forests in early modern English literature, this book is the first to identify 'sylvan pastoral' as a distinct literary form and thus makes an important contribution to the growing field of ecocriticism and the history of environmentalism"--Provided by publisher.